Social Accountability Review : Forestry Sector in Moldova - World Bank (Washington, DC, 2014)
The forestry sector in Moldova faces significant governance and sustainability challenges. The insufficient level of forest coverage in Moldova has a serious impact on environment and overall economic growth in the country. The situation is exacerbated by the reportedly intense pressure on forest resources exerted by the human factor. Illegal logging and grazing are considered as significant factors that contribute to forest loss. There is a lack of public demand for sustainable forest management. Social accountability (SA) has been recognized as an effective mechanism to improve government service delivery and enhance developmental impact. SA mechanisms entail a broad range of approaches that enable citizens to access governmental information, lodge grievances and receive redress, oversee the provision of governmental services, and take an active part in management and decision-making processes. This report aims to review SA mechanisms that are currently available in the forestry sector in Moldova and identify opportunities for improvement.